(untitled) - Gogol, Sara (Terre Haute, Ind., 2002)
An in-depth look at the challenging lives of women coaches, Hard Fought Victories, profiles coaches of a wide variety of sports -- including basketball, volleyball, tennis, softball, track, soccer, rowing, field hockey, cross country and ice hockey -- at U.S. colleges. Among them are older women who have witnessed enormous changes for female athletes and know firsthand the history behind those changes, and younger women just starting out in the coaching field, whose lives offer a glimpse of the future for women's sports.
Keywords: Coaches (Athletics),Huấn luyện viên (Thể thao); United States,Hoa Kỳ